GRP78 (Glucose-Regulated Protein of 78 kDa) Promotes Cardiomyocyte Growth Through Activation of GATA4 (GATA-Binding Protein 4). Issue 2 (February 2019) - Zhang, Guangyu; Wang, Xiaoding; Bi, Xukun; Li, Chao; Deng, Yingfeng; Al-Hashimi, Ali A.; Luo, Xiang; Gillette, Thomas G.; Austin, Richard C.; Wang, Yanggan; Wang, Zhao V.
Abstract : The heart manifests hypertrophic growth in response to elevation of afterload pressure. Cardiac myocyte growth involves new protein synthesis and membrane expansion, of which a number of cellular quality control machineries are stimulated to maintain function and homeostasis. The unfolded protein response is potently induced during cardiac hypertrophy to enhance protein-folding capacity and eliminate terminally misfolded proteins. However, whether the unfolded protein response directly regulates cardiac myocyte growth remains to be fully determined. Here, we show that GRP78 (glucose-regulated protein of 78 kDa)—an endoplasmic reticulum-resident chaperone and a critical unfolded protein response regulator—is induced by cardiac hypertrophy. Importantly, overexpression of GRP78 in cardiomyocytes is sufficient to potentiate hypertrophic stimulus-triggered growth. At the in vivo level, TG (transgenic) hearts overexpressing GRP78 mount elevated hypertrophic growth in response to pressure overload. We went further to show that GRP78 increases GATA4 (GATA-binding protein 4) level, which may stimulate Anf (atrial natriuretic factor) expression and promote cardiac hypertrophic growth. Silencing of GATA4 in cultured neonatal rat ventricular myocytes significantly diminishes GRP78-mediated growth response. Our results, therefore, reveal that protein-folding chaperone GRP78 may directly enhance cardiomyocyte growth by stimulating cardiac-specific transcriptional factor GATA4. Abstract : Supplemental Digital Content is available in the text.